Fluorescence pH-dependent sensing of zinc (II) and chromium (III) cations by a tripodal ligand and exploration of emission response in solution and in the solid state. (September 2021) - Diana, Rosita; Caruso, Ugo; Di Costanzo, Luigi; Gentile, Francesco Silvio; Panunzi, Barbara
Abstract: A tripodal colorimetric chemosensor named PoPAP was used as a fluorescence probe towards the first-row transition cations. A real-time fluorescence enhancement in presence of zinc (II) and chromium (III) cations was detected in slightly acidic water solution. The same cations partially quenched the emission of the ligand in basic medium. As function of pH conditions, different coordination modes of the chemosensor in complex with zinc (II) were isolated and analyzed. Fluorescence color difference of PoPAP in complex with zinc allows for an easy detection by naked-eye at acidic and basic conditions. The solid forms of PoPAP in complex with zinc show a reduction to about one third of the fluorescence quantum yield as compared with the value in its unbound form and due to ACQ phenomena. DFT calculations, starting from single crystal structure analysis are in good agreement with the experimental emission patterns. Two different mechanisms of electron density transfer from ground to excited state were analyzed as function of pH conditions. Graphical abstract: Image 1 Highlights: Fluorescence sensing by a tripodal chemosensor in solution and in the solid state. Fluorescence enhancement in zinc (II) and chromium (III) aqueous solution. Different pH produced selective emission patterns.